Gulyaxojayorovna@gmail.com THE PROFESSIONAL COMPETENCE OF MODERN TEACHERS: THE PROFESSIONAL COMPETENCE OF MODERN TEACHERS - Musurmonqulova, Gulhayo (Журнал иностранных языков и лингвистики, 2022)
The quality of education is a central theme in education systems. The quality of education is increasingly judged by focusing on pupils‟ performance, what pupils actually learn, and how well they learn it.